2006
DOI: 10.1111/j.1468-0017.2006.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Effort and Effects in Metaphor Comprehension: Relevance Theory and Psycholinguistics

Abstract: This paper explores the trade-off between cognitive effort and cognitive effects during immediate metaphor comprehension. We specifi cally evaluate the fundamental claim of relevance theory that metaphor understanding, like all utterance interpretation, is constrained by the presumption of optimal relevance ( Sperber and Wilson, 1995 , p. 270): the ostensive stimulus is relevant enough for it to be worth the addressee ' s effort to process it, and the ostensive stimulus is the most relevant one compatible with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(62 citation statements)
references
References 36 publications
2
60
0
Order By: Relevance
“…In summary, Noveck et al say, ''The work reported here shows that metaphors can be seen to be costly in contexts that are arguably neutral otherwise'' (Noveck et al, 2001: 119). Gibbs and Tendahl (2006) questioned the generality of Noveck et al's experimental findings, and their conclusions about metaphor processing in neutral contexts. First, Noveck et al only compared non-metaphorical referring expressions (e.g., ''All children to the side of the pool'') against metaphorical referring expressions (e.g., ''All toads to the side of the pool''), the latter of which both picks out a referent and expresses a property attribution, unlike the first expression which is only referential.…”
Section: Pragmatics and Online Metaphor Usementioning
confidence: 96%
See 2 more Smart Citations
“…In summary, Noveck et al say, ''The work reported here shows that metaphors can be seen to be costly in contexts that are arguably neutral otherwise'' (Noveck et al, 2001: 119). Gibbs and Tendahl (2006) questioned the generality of Noveck et al's experimental findings, and their conclusions about metaphor processing in neutral contexts. First, Noveck et al only compared non-metaphorical referring expressions (e.g., ''All children to the side of the pool'') against metaphorical referring expressions (e.g., ''All toads to the side of the pool''), the latter of which both picks out a referent and expresses a property attribution, unlike the first expression which is only referential.…”
Section: Pragmatics and Online Metaphor Usementioning
confidence: 96%
“…How might these different cognitive effects be manifested with metaphor? One experimental study investigated people's understanding of metaphorical statements, like ''Lawyers are also sharks'' in contexts where a speaker provided new information by using the metaphor, strengthening an existing assumption, and contradicting an existing assumption (Gibbs and Tendahl, 2006). Each of these different meanings is related to the basic metaphorical understanding of the comparison between ''lawyers'' and ''sharks.''…”
Section: Pragmatics and Online Metaphor Usementioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the alleged ad hoc concept BUTCHER* is easily accessed. A third possibility is to claim, following the line of Gibbs and Tendahl (2006), that there is no systematic answer to such a question. Accessibility is simply a contextual affair, and there are no neutral contexts to evaluate how much effort is needed by a specific interpretation.…”
Section: Metaphor In Relevance Theorymentioning
confidence: 99%
“…This general question of an integration of cognitive and communicative aspects in metaphor theory has recently become the subject of intensive theoretical and methodological discussions which focus on the relationship between CMT and specifically Relevance-theoretically (RT) oriented analyses (Carston & Wearing, 2011;Gibbs & Tendahl, 2006Sperber & Wilson, 1995Tendahl, 2009;Tendahl & Gibbs, 2008;Wilson, 2011;Wilson & Carston, 2006). This discussion can serve as a platform to sketch future perspectives in which metaphor research can contribute to CDA.…”
Section: Critical Discourse Studiesmentioning
confidence: 99%